Ovicillium sinense, a new species from Guizhou, China - Chen, Wan-Hao; Li, Dan; Wei, Yan-Jun; Liang, Jian-Dong; Han, Yan-Feng (Phytotaxa, 2024)
A new species, Ovicillium sinense, which was isolated from an infected pupa, is introduced. Morphological comparisons with extant species and DNA-based phylogenies from analysis of a multigene dataset of combined ITS, LSU and TEF sequence data support the establishment of the new species. It differs from other species by its phialides that are attenuated from the middle to the apex, the conidia aggregated in large globose to subglobose heads, and having shorter phialides and smaller conidia.